2009
DOI: 10.1002/yea.1679
|View full text |Cite
|
Sign up to set email alerts
|

Fed‐batch methanol feeding strategy for recombinant protein production by Pichia pastoris in the presence of co‐substrate sorbitol

Abstract: Batch-wise sorbitol addition as a co-substrate at the induction phase of methanol fed-batch fermentation by Pichia pastoris (Mut + ) was proposed as a beneficial recombinant protein production strategy and the metabolic responses to methanol feeding rate in the presence of sorbitol was systematically investigated. Adding sorbitol batch-wise to the medium provided the following advantages over growth on methanol alone: (a) eliminating the long lag-phase for the cells and reaching 'high cell density production' … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
76
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 97 publications
(83 citation statements)
references
References 40 publications
(46 reference statements)
6
76
1
Order By: Relevance
“…Although the former protein is encoded by a putative ldhA gene of P. pastoris (not annotated in S. cerevisiae), considering the fact that ethanol does not accumulate in P. pastoris medium (Cereghino and Cregg, 2000), a direct reduction of the intracellular pyruvate to lactate could be the alternative pathway for the NAD þ regeneration. Thus, lactate was included in the model, since its accumulation was previously observed in P. pastoris extracellular medium (Ç elik et al, 2009;Xie et al, 2005).…”
Section: Mass Flux Balance-based Analysismentioning
confidence: 99%
“…Although the former protein is encoded by a putative ldhA gene of P. pastoris (not annotated in S. cerevisiae), considering the fact that ethanol does not accumulate in P. pastoris medium (Cereghino and Cregg, 2000), a direct reduction of the intracellular pyruvate to lactate could be the alternative pathway for the NAD þ regeneration. Thus, lactate was included in the model, since its accumulation was previously observed in P. pastoris extracellular medium (Ç elik et al, 2009;Xie et al, 2005).…”
Section: Mass Flux Balance-based Analysismentioning
confidence: 99%
“…Thereafter, Jungo et al 4 performed methanol/sorbitol mixed fed-batch bioreactor experiments for recombinant avidin production using P. pastoris Mut + phenotype and reported that accumulation of sorbitol in the medium does not affect the specific recombinant protein productivity. In a recent study Ç elik et al 5 investigated the effect of batch-wise sorbitol addition in the fed-batch production phase for glycosylated protein, recombinant human erythropoietin (rHuEPO) production by P. pastoris-EPO-Mut + strain, and concluded that the simultaneous utilization of sorbitol and methanol not only decreased the process time but also increased the product yield on substrate.…”
Section: Introductionmentioning
confidence: 98%
“…2 -5 Typically, either a three-or four-stage fed-batch operating strategy is utilized for the production of r-proteins. 6,2,5 In a three-stage process, first, in order to accumulate cells, the engineered strain is cultured in defined medium containing glycerol, a non-fermentable but repressing carbon source (Phase I). Second, a fed-batch transition phase is applied in which glycerol is fed to the bioreactor at limiting levels to further increase cell concentration (Phase II).…”
Section: Introductionmentioning
confidence: 99%
“…Most studies have reported the mixture of multicarbon substrates for P. pastoris growth and for foreign protein expression [Celik et al, 2009;Wang et al, 2010]. Few reports can be found on alternative convenient organic nitrogen sources for P. pastoris to express heterologous proteins.…”
Section: Discussionmentioning
confidence: 99%